Immune responses of cattle to African trypanosomes: Protective or pathogenic? - Taylor, K.A. (Elsevier, 1998)
Trypanosomosis in domestic livestock negatively impacts food production and economic growth in many parts of the world, particularly in sub-Saharan Africa. Current methods of control are inadequate to prevent the enormous annual socio-economic losses resulting from this disease. Hope for a vaccine based on the variant surface glycoprotein coat was abandoned several years ago when the complexity of the parasite's antigenic reportoire was appreciated. As a result, research is now focused on identifying invariant trypanosome components as potential targets fro interrupting infection or infection-mediated disease. The identification of immune mechanisms involved in parasite and disease control or conversely those responses that are associated with a poor clinical outcome should facilitate the search for vaccine candidates and subsequent vaccine design strategies. To this end, comparative studies on the immune responses of trypanotolerant and trypanosusceptible breeds of cattle can be exploited. These studies have revealed that trypanotolerant and trypanosusceptibel breeds of cattle have distinct antibody responses. Trypanosusceptible cattle produce high titres of polyspecific IgM but fail to produce IgG to specific trypanosome antigens. In contrast, although T cell and macrophage monocyte responses of infected cattle are depressed significant differences have not been described between tolerant and susceptible breeds of cattle. In this review isotype-dependent effector mechanisms such as complement activation binding to Fc receptors activation of phagocytic cells neutralisation of parasite components clearance of immune complexes and autommune responses are discussed in the context of their potential impact on either susceptibility or tolerance of cattle to trypanosomosis. In addition the links between specific cytokine patterns macrophage/monocyte activation and depressed T cell responses that occur during trypanosome infection are presented. The identification of mechanisms that mediate depressed immune responses might suggest novel disease intervention strategies.